Adubação e irrigação de café: adubação combinada com irrigação no primeiro ano da instalação das covas - Graner, E. A.; Godoy Junior, C.; Godoy, O. Pereira (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1961)
This paper deals with different types of fertilizer applications in coffee hill in the moment of transfering the plants to the field. During the first year, irrigation was applied in the dry season. After one year, the following characters were analised: plant height; plant diameter; number of productive branches; lenght and number of nodes in the first branch of the plant. The results obtained can be summarized as follows: the irrigation employed did not affect the treatments and mineral fertilizers combined with organic fertilizer were better than the others treatments used for comparisons.